2014
DOI: 10.1111/ecog.00779
|View full text |Cite
|
Sign up to set email alerts
|

A framework for evaluating the influence of climate, dispersal limitation, and biotic interactions using fossil pollen associations across the late Quaternary

Abstract: Environmental conditions, dispersal lags, and interactions among species are major factors structuring communities through time and across space. Ecologists have emphasized the importance of biotic interactions in determining local patterns of species association. In contrast, abiotic limits, dispersal limitation, and historical factors have commonly been invoked to explain community structure patterns at larger spatiotemporal scales, such as the appearance of late Pleistocene no‐analog communities or latitudi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
146
2
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(151 citation statements)
references
References 62 publications
0
146
2
3
Order By: Relevance
“…The first 'Classic framework' has been recently proposed and applied to examine taxon associations through time for late Quaternary fossil pollen assemblages at relatively large spatial extent and small spatial grain (Blois et al 2014). The first 'Classic framework' has been recently proposed and applied to examine taxon associations through time for late Quaternary fossil pollen assemblages at relatively large spatial extent and small spatial grain (Blois et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The first 'Classic framework' has been recently proposed and applied to examine taxon associations through time for late Quaternary fossil pollen assemblages at relatively large spatial extent and small spatial grain (Blois et al 2014). The first 'Classic framework' has been recently proposed and applied to examine taxon associations through time for late Quaternary fossil pollen assemblages at relatively large spatial extent and small spatial grain (Blois et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Diamond (1975) proposed that species coexistence is regulated by 'community assembly rules' based primarily on species interactions, and inferred these rules from the pattern of species co-occurrence in replicated island assemblages. Since then, the search for community assembly rules has dominated community ecology (Gotelli and Graves 1996, Ovaskainen et al 2010, Boulangeat et al 2012, HilleRisLambers et al 2012, Blois et al 2014), and null model analysis has become a standard tool to search for patterns that may reflect processes of community assembly (Gotelli and Ulrich 2012). Since then, the search for community assembly rules has dominated community ecology (Gotelli and Graves 1996, Ovaskainen et al 2010, Boulangeat et al 2012, HilleRisLambers et al 2012, Blois et al 2014), and null model analysis has become a standard tool to search for patterns that may reflect processes of community assembly (Gotelli and Ulrich 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such modern-day corroborations are stimulating novel analyses of living populations in light of geologic history, finding, for example, that present-day endemism is most strongly correlated with the velocity of postglacial climate change rather than with a threshold temperature or particular direction of change (86) and that populations along the margin of a species' range still exhibit low genetic diversity, a legacy of Quaternary expansion (87). Young fossil records alone show (i) just how pervasive changes in species' distributions are likely to become, constituting both local losses and additions, (ii) that novel groupings are most likely to emerge near the edges rather than centers of biogeographic provinces or ranges (88,89), (iii) that species most able to cross former boundaries and those showing strongest population declines are not random draws from their parent community (79,90), and (iv) that species associations suggesting biotic interactions are rare and inconstant (91).…”
Section: Proxy Evidence Of (Paleo)environmentalmentioning
confidence: 99%
“…However, these authors used indirect evidence within the community assembly framework that assumes that overdispersion of phylogenetic and functional traits is a consequence of competitive interactions (Darwin’s competition-relatedness hypothesis, reviewed in Allan et al 2013, Götzenberger et al 2012) [8586]. However, Cahill et al (2008) [87] found little evidence for this assertion and it is now well known that overdispersion (spatial segregation) might stem from different processes, particularly from filter effects within heterogeneous landscapes [88] and even from dispersal limited neutral community assembly [89]. Here we used a direct way to assess whether any set of competitive strength relationships between species is able to predict observed abundance distributions.…”
Section: Discussionmentioning
confidence: 99%